If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(3d + -4) = 6 Reorder the terms: 5 + -1(-4 + 3d) = 6 5 + (-4 * -1 + 3d * -1) = 6 5 + (4 + -3d) = 6 Combine like terms: 5 + 4 = 9 9 + -3d = 6 Solving 9 + -3d = 6 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -3d = 6 + -9 Combine like terms: 9 + -9 = 0 0 + -3d = 6 + -9 -3d = 6 + -9 Combine like terms: 6 + -9 = -3 -3d = -3 Divide each side by '-3'. d = 1 Simplifying d = 1
| 3n/7-1=1/8 | | 3-8c=25 | | 6x-(-6)= | | 2a/3+8/9=4 | | 12-2m=-18 | | 4x-14=-82 | | 40=50*(1-r) | | 2-6x=-4x+1 | | 8x-4=x+10 | | 2p=-256 | | 30+6x=5x | | x+439=(x-58)2 | | 2(m+4)=m+2 | | 78+r=-76 | | 151(57457+9)+9252=1 | | x=x^2-x-12 | | 6(x+3)=10 | | ln(x+2)+ln(x)=ln(x+12) | | 0.50x+0.35(50)=47.5 | | 6(x-3)=10 | | -12/9-30/-12= | | 3f+15=51 | | -2.8=w | | 400*400= | | x*x+1200=2x*2x | | R(6-s-t)+6p(6-s-t)= | | -2c+2=5c | | 3=14+2x | | 6x+(x+1)=5(x+1) | | 4x^2-5x+9=2x+6 | | x+x+x+x=30 | | -(-n)=1 |